Donner forme à la doctrine de l’élection : « La voie du salut » d’Antoine Garissoles (Montauban, 1637) - Daniel Bolliger (Cahiers d'Études du Religieux- Recherches Interdisciplinaires, 2010)
The collection of eight catechetical sermons of the preacher and professor Antoine Garissoles (1587-1651), published in 1637 under the title of « la voye du salut [the way of salvation] », presents the typical multiple aspects of the early modern sermon at the crossroads of the confessional doctrine in its evolution, the paduan neoaristotelianism as the dominating philosophy of its time and of the articulations of a piety with more and more traits of subjectivity. These interrelations, still scarcely explored for the french protestant sermon at the beginning of the seventeenth century, are assembled in the composition of the “voye” which chooses an approach to one of the main subjects of Calvinism, divine election, in the lines of zabarellism. Garissoles’s homiletic procedure along an eightfold series, the usual superstructure for catechetical sermons, offers itself quite naturally for this analytical process since, as the methodus resolutiva starts out with the end of a human activity in order to develop the means required to it, the scheme of the collection heeds off a key topic, elaborates it, for finally letting it culminate in an applicative conclusion completing the whole collection.